Farm power and machinery management : laboratory manual and workbook - Hunt, Donnell (Ames : Iowa State University Press, 1977)
The objective of this text are to analyze the factors that comprise machinery management, to explain the function of the various machines and mechanisms as they affect economic operation, and to indicate approaches and procedures for making management decisions.
rpm 31/01/2019
Loans
Keywords: Agricultural machinery; Farm mechanization